2003
DOI: 10.1074/jbc.m210992200
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of c-Jun NH2-terminal Kinase (JNK) by DNA-damaging Agents Serves to Promote Drug Resistance via Activating Transcription Factor 2 (ATF2)-dependent Enhanced DNA Repair

Abstract: The activating transcription factor 2 (ATF2) is a member of the ATF/cAMP-response element-binding protein family of basic-leucine zipper proteins involved in cellular stress response. The transcription potential of ATF2 is enhanced markedly by NH 2 -terminal phosphorylation by c-Jun NH 2 -terminal kinase (JNK) and mediates stress responses including DNA-damaging events. We have observed that four DNA-damaging agents (cisplatin, actinomycin D, MMS, and etoposide), but not the cisplatin isomer, transplatin, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
119
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 61 publications
8
119
0
Order By: Relevance
“…ERK is known to respond to both oxidative stress and alkylating agents [38]. Notably, our data would suggest that ERK is perhaps more sensitive to oxidative stress than alkylating agents since HEK 293 cells exposed to hydrogen peroxide accumulated roughly twice as much nuclear S3 as did exposure to the two alkylating agents when cell survival was at 70%.…”
Section: Discussionmentioning
confidence: 70%
“…ERK is known to respond to both oxidative stress and alkylating agents [38]. Notably, our data would suggest that ERK is perhaps more sensitive to oxidative stress than alkylating agents since HEK 293 cells exposed to hydrogen peroxide accumulated roughly twice as much nuclear S3 as did exposure to the two alkylating agents when cell survival was at 70%.…”
Section: Discussionmentioning
confidence: 70%
“…This data are in agreement with a previous study reporting a correlation between ATF2 expression and the resistance to CDDP treatment in breast carcinoma BT474 cell line. 8 In details, Shah et al identified the same nuclear punctiform pattern shown in Figure 2 and concluded that such peculiar staining could indicate ATF2 localization in DNA repair foci following DNA damage. 35 Our results indicate that Celastrol, an active triterpene extracted by the Chinese herb "Thunder of God Vine", downmodulates ATF2-mediated transcription in a dose dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…ATF2 is a member of the helix-loop-helix b-ZIP transcription factor family, often associated to chemo-and radioresistance. 8,33 Agents that inhibit ATF2 activate, both in vitro and in vivo, apoptotic pathways leading to an increased response to radio-and chemo-therapy. 34 In the present study, we reported a correlation between ATF2 protein expression, as total and phosphorylated form, and CDDP resistance ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations